# Give the values a, b, and c needed to write the equations standard form. 2/3(x - 4)(x + 5)=1

**Solution:**

Given equation is 2/3(x - 4)(x + 5)=1

The standard form of the quadratic equation is ax^{2}+bx+c=0 Where a, b are the coefficients of x, and c is the constant term. The first condition for an equation to be a quadratic equation is that the coefficient of x^{2} is a non-zero term(a ≠0). For writing a quadratic equation, the numeric values of a, b, c are generally not written as fractions or decimals but are written as integral values.

Cross multiplying the terms of the given equation 2/3 (x - 4) (x + 5)=1

2(1) = 3(x - 4)(x + 5)

2 = 3[x^{2}- 4x + 5x + 20]

2 = 3[x^{2} + x +20]

2 = 3x^{2} + 3x + 60

2 = 3x^{2} + 3x + 60

3x^{2} + 3x + 60 - 2 = 0

3x^{2} + 3x + 58 = 0.

The equivalent quadratic form of the given equation is 3x^{2} + 3x + 58 = 0.

Comparing the equation 3x^{2}+ 3x + 58 = 0 with the standard form of quadratic equation ax^{2}+bx+c=0

a =3 ,b= 3 and c =58

## Give the values a, b, and c needed to write the equations in standard form. 2/3(x-4)(x+5)=1

**Summary:**

The values of a,b and c so that the equation23(x-4)(x+5)=1 in the standard quadratic equation are a =3 ,b= 3 and c =58